GeoSMART; A New Approach for Geography Learning in the 21st Century - Nofrion, Nofrion; Rahmanelli, Rahmanelli; Ismail, Aziah; Malik, Abid; Utomo, Erwin Pri; Operma, Sukron (Journal of Learning Improvement and Lesson Study, 2024)
The development of human life in the 21st century requires teachers to be more creative in designing learning that is more interesting, challenging and impressive. Interesting learning is learning that is presented with the teacher’s brilliant ideas in the form of methods, media and learning resources. Challenging learning can be defined as learning that is able to develop students’ reasoning, critical thinking and analytical skills. Meanwhile, impressive learning is learning that is framed by example, character and universal human values. The GEOSMART approach was developed as an alternative solution to the problem of Geography learning which is still teacher-centred, has minimal student involvement and limited use of technology. There are five elements in the GEOSMART approach, namely, 1) scientific, 2) measurable, 3) applicable, 4) reasoning and 5) technology. Development is carried out using the Plomp model. The results of validation by experts show that the development product is in the very valid category. Meanwhile, the practicality test results show that the development product is in the very practical category. The results of effectiveness tests based on the results of experimental research in seven schools in West Sumatra show that the GeoSMART approach can improve student learning outcomes, especially student involvement in learning and critical thinking abilities.